Differences in carrier frequency between mothers of Duchenne and Becker muscular dystrophy patients - Lee, Tomoko (Nature Publishing Group, 2014)
Duchenne and Becker muscular dystrophies (DMD/BMD) are X-linked inherited muscular disorders caused by mutations in the dystrophin gene. Two-thirds of DMD cases are thought to be caused by inheritance from carrier mothers and this study aimed to clarify and compare the carrier frequency of mothers of DMD and BMD patients according to the mutation type. We included 139 DMD and 19 BMD mothers. Of these, 113 patients (99 DMD and 14 BMD) and 13 patients (12 DMD and 1 BMD) had deletions and duplications of one or more exons, respectively. Small mutations, including nonsense mutations, small deletions/insertions and splice site mutations, were identified in 32 patients (28 DMD and four BMD). The overall carrier frequency for BMD mothers was significantly higher than for DMD (89.5% vs 57.6%, P<0.05), probably as BMD patients can leave descendants. The carrier frequency tended to be lower in mothers of DMD patients with deletion mutations than with duplications and small mutations (53.5%, 66.7% and 67.9%, respectively). It was suggested that de novo mutations are more prevalent for deletions than other mutations. This is the first report to analyze the carrier frequency according to mutation type.